2019
DOI: 10.1021/acsnano.8b09754
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Chirality Definable Growth of Single-Walled Carbon Nanotubes

Abstract: In order to achieve the chirality-specific growth of single-walled carbon nanotubes (SWCNTs), it is crucial to understand the growth mechanism. Even though many molecular dynamics (MD) simulations have been employed to analyze the SWCNT growth mechanism, it has been difficult to discuss the chirality determining kinetics because of the defects remaining on the SWCNTs grown in simulations. In this study, we demonstrate MD simulations of defect-free SWCNTs, that is, chirality definable SWCNTs, under the optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…268 A recent MD simulation by Maruyama et al showed that an adjacent pair of pentagon− heptagon changes the chirality to (0,±1), (±1,0), (−1,1), or (1,−1). 269 The chirality change will be greater, (0,±2), (0,±3), and so on, if the pentagon is away from heptagon. How to achieve a single dominant (n,n − 1) species is still a mystery because it is very difficult to control the number of pentagon− heptagon pairs and their locations.…”
Section: Structure-controlled Growth Of Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…268 A recent MD simulation by Maruyama et al showed that an adjacent pair of pentagon− heptagon changes the chirality to (0,±1), (±1,0), (−1,1), or (1,−1). 269 The chirality change will be greater, (0,±2), (0,±3), and so on, if the pentagon is away from heptagon. How to achieve a single dominant (n,n − 1) species is still a mystery because it is very difficult to control the number of pentagon− heptagon pairs and their locations.…”
Section: Structure-controlled Growth Of Swcntsmentioning
confidence: 99%
“…However, there are at least six possibilities of ( n , m ) switching, including ( n , m ± 1), ( n ± 1, m ), ( n + 1, m – 1), and ( n – 1, m + 1), when an adjacent pair of pentagon–heptagon is incorporated in a tube . A recent MD simulation by Maruyama et al showed that an adjacent pair of pentagon–heptagon changes the chirality to (0,±1), (±1,0), (−1,1), or (1,–1) . The chirality change will be greater, (0,±2), (0,±3), and so on, if the pentagon is away from heptagon.…”
Section: Structure-controlled Growth Of Swcntsmentioning
confidence: 99%
“…The growth mechanism of SWCNTs involving aspects of thermodynamics and kinetics revealed by computer [83,84,[110][111][112][113][114][115] and in-situ techniques [85,86,[116][117][118][119][120][121][122][123][124] became clearer. As to chirality-based sorting, Kataura et al demonstrated industrial-scale separation of high-purity, single-chirality SWNTs by using mixedsurfactant gel chromatography [125] and the separation of 12 different single-chirality enantiomers with high enantiomeric purity [126].…”
Section: Brief Summary Of Controlled Synthesis Of Cntsmentioning
confidence: 99%
“…[ 24,26,130 ] It was reported that any defects such as the pentagon‐heptagon pair in a SWCNT will change the local chirality. [ 131‐133 ] When disturbing the growth parameters during CVD, such as changing carbon feeding stocks [ 88,134 ] and introducing an electric field, [ 135 ] the as‐grown SWCNTs exhibited heterojunctions with different chiralities. With this strategy, the SWCNTs with high‐ purity electronic type [ 135 ] and specific chirality were obtained.…”
Section: Structure‐controlled Growth Of Carbon Nanotubes With Well‐defined Catalystsmentioning
confidence: 99%